Development of a nucleocapsid protein-based competitive ELISA for the detection of porcine deltacoronavirus antibodies - Han, Shuizhong; Zhou, Yu; Li, Maiping; Chen, Penggang; Huang, Xingming; Wang, Ying (Frontiers in Microbiology, 2025)
Porcine deltacoronavirus (PDCoV) is a significant threat to the global swine industry, causing severe diarrhea in piglets and exhibiting a broad host range with zoonotic potential. The nucleocapsid (N) protein of PDCoV is highly conserved and immunogenic, making it an ideal target for diagnostic development. However, existing enzyme-linked immunosorbent assays (ELISAs) typically rely on enzyme-labeled secondary antibodies, complicating the experimental procedure. In this study, a monoclonal antibody (mAb 3C6) against the PDCoV N protein was developed and utilized to establish a competitive ELISA (cELISA). The recombinant N protein (~40 kDa) was successfully expressed and purified. Epitope mapping identified the linear B-cell epitope recognized by mAb 3C6 as 121-HQLLPLRFPTGDGPA-135. Using 60 PDCoV-negative serum samples, the cut-off value for the cELISA was determined to be 44.3%. Validation with 175 field swine serum samples demonstrated a diagnostic sensitivity of 88.5%, specificity of 92.6%, and an overall agreement of 92.0%. The cELISA showed analytical sensitivity twice that of an indirect immunofluorescence assay (IFA) and detected PDCoV-specific antibodies as early as 7 days post-infection. No cross-reactivity with other common swine pathogens was observed. The coefficients of variation for intra- and inter-assay reproducibility ranged from 4.39 to 9.20% and 4.20 to 7.97%, respectively. In conclusion, the developed N protein-based cELISA represents a reliable and efficient tool for the serological detection of PDCoV.